MASYARAKAT DAN TANAH ADAT DI BALI (Studi Kasus Kabupaten Buleleng, Provinsi Bali) - S. Hendriatiningsih; A. Budiartha; Andri Hernandi (Fakultas Seni Rupa dan Desain ITB, 2008)
Land has a real important meaning and function. Customary communitie obtains the right to master deep soil meaning of exploiting land. Existence of this customary land generates various form of land tenure in customary communities In consequence boundary a plot of land and also regional become of vital importance. So do like in Bali, countryside pakraman is federation of customary law which still growing in Indonesia which the existence accompaniment with desa/kelurahan which is notched by goverment. Pakraman has various customary land types and the boundary object. With classification will be seen land right which stick with the customary land and the determination type of boundary applied. Classification will referens from various customary land types in UUPA. Pakraman arranges its region and arranges usage of his own customary land, but ownership of by pakraman and stipulating of boundary can be told is unclear by the national law. Kata kunci : desa pakraman, tanah adat, batas. Keyword : countryside pakraman, customary land, the boundary.